BIMBINGAN TEKNIS BAGI ANGGOTA LEMBAGA PERLINDUNGAN KONSUMEN GERAKAN PERUBAHAN INDONESIA (GPI) DEWAN PIMPINAN DAERAH KABUPATEN LAMPUNG BARAT - Purwanti, Yuli; Rachman, Fathur; Lutfi, M.; Aryani, Gustina; Surya Pratama, Satrya; Renaldy, Rendy; Gunawan, Tedi (Jurnal Media Pengabdian Kepada Masyarakat, 2023)
Technical guidence for all over member consumer protection agency Gerakan Perubahan Indonesia (LP-GPI) need to be emplemented to provide supplies sciencein the legal field consumer protection, before the members LPK-GPI wider plunge into society. Verious aspects consumer protection given on activitythis technicsl guidance. Problem approach use approach normative and empirical approach that is by doing outreach activities and technical guidance. Data types cansist of primary blood and secondary data. Data collection done whit literature study and field study. Data alalysis whit qualitative analiysis. Society in general do not understand about consumer protection law about their rights and obligation as a consumer dan many caseshappen regerding so that three is a need accompaniment for society relatedto consumer